Challenging the Black Atlantic : The New World Novels of Zapata Olivella and Gonçalves - Maddox, John Thomas, IV, 1981- (Book collections on Project MUSE., 2021)
"The historical novels of Manuel Zapata Olivella and Ana Maria Gonçalves map black journeys from Africa to the Americas in a way that challenges the Black Atlantic paradigm that has become synonymous with cosmopolitan African diaspora studies. Unlike Paul Gilroy, who coined the term and based it on W.E.B. DuBois's double consciousness, Zapata, in Changó el gran putas (1983), creates an empowering mythology that reframes black resistance in Colombia, Haiti, Mexico, Brazil, and the United States. In Um defeito de cor (2006), Gonçalves imagines the survival strategies of a legendary woman said to be the mother of black abolitionist poet Luís Gama and a conspirator in an African Muslim-led revolt in Brazil's "Black Rome." These novels show differing visions of revolution, black community, femininity, sexuality, and captivity. They skillfully reveal how events preceding the UNESCO Decade of Afro-Descent (2015-2024) alter our understanding of Afro-Latin America as it gains increased visibility"--